Creating a Shared Neuroscience Collection Development Policy - Ketterman, Elizabeth; Hoover, Jeanne K.; Cable, Kathy (My University, 2012)
At East Carolina University (ECU), Joyner Academic and Laupus Health Sciences Libraries collaborated on a shared Neuroscience collection development policy, primarily as a reaction to state-level budget cuts. The policy aims to limit duplication in purchases at each library location but also describes the materials that are most appropriate for selection by each library and explores the usefulness of e-book purchases as a cost-saving measure. The result of this collaborative effort is a comprehensive neuroscience collection for ECU's libraries.
This is the final version of the article before it was published. For the published version, please see the Journal of Electronic Resources in Medical Libraries.
Keywords: Library collaboration; Collection development policies; E-books; Neuroscience; Biology, Neuroscience